IDENTIFYING THE CHARACTERISTICS OF PRISONERS IN DRUG CASES TO REDUCE ANTISOCIAL BEHAVIOR IN THE BONDOWOSO CLASS IIB PRISON - Girindra Muhammad Afrell; Umar Anwar; Budi Priyatmono; Ali Muhammad (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study explores the thought patterns and attitudes of inmates convicted of drug-related offenses at the Class IIB Correctional Institution in Bondowoso, with a focus on understanding the factors that contribute to repeated offending. The research is motivated by the high rate of recidivism in drug cases, which raises concerns about inmates’ awareness, mindset, and readiness to change. Using a qualitative case study approach, data were collected through in-depth interviews with inmates, religious mentors, correctional officers, and health professionals. Thematic analysis was applied to identify recurring patterns and key insights. The findings reveal that many inmates tend to justify their past actions, feel comfortable in negative environments, and display excessive optimism about avoiding legal consequences. Impulsive decision-making without careful consideration is also common. Although some inmates express a desire to change, their efforts are often inconsistent and easily influenced by emotional and social pressures. Participation in rehabilitation or religious programs is not always based on genuine motivation, but sometimes driven by formal obligations or personal strategy. The study concludes that these unhealthy thought patterns and attitudes hinder meaningful behavioral change. Therefore, rehabilitation efforts need to be more personalized, in-depth, and continuous, with a stronger emphasis on developing self-awareness, accountability, and internal motivation to support lasting transformation and reduce recidivism. Keywords: Inmate Characteristics; Narcotics Inmates; Deviant Behavior